Legal Framework for Authenticity of Blockchain Electronic Evidence in China: Under a Comparative Law Perspective - Chen, Siqi; Rajamanickam, Ramalinggam; Manap, Nazura Abdul (Faculty of Law, Hasanuddin University, 2024)
This article analyses the attitudes of various courts towards blockchain electronic evidence and the inconsistent conclusions on its authenticity in China’s judicial practice. The purpose of this article is to explore the rules for determining the authenticity of blockchain electronic evidence that are suitable for China’s reality. This article adopts a qualitative approach to analyse the rules for determining the authenticity of blockchain electronic evidence in China, and identifies the problems faced when reviewing the authenticity of blockchain electronic evidence in Chinese judicial practice. Finally, by comparing and learning from the U.S. rules for determining the authenticity of blockchain electronic evidence, this article puts forward proposals for establishing the best evidence rule and the hearsay rule for blockchain electronic evidence, refining the rules for judicial presumptions as well as explicitly reviewing the authenticity of the electronic evidence prior to uploading it to the blockchain.